2017
DOI: 10.1021/acs.analchem.7b03609
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Analysis of Lactosylceramide, Galabiosylceramide, and Globotriaosylceramide by LC-MS/MS in Urine of Fabry Disease Patients

Abstract: Fabry disease is an X-linked lysosomal storage disorder caused by α-galactosidase A (α-GAL A) deficiency. This enzyme contributes to the cellular recycling of glycosphingolipids such as galabiosylceramide (Ga), globotriaosylceramide (Gb), and globotriaosylsphingosine (lyso-Gb) by hydrolyzing the terminal α-galactosyl moiety. Urine and plasma α-GAL A substrates are currently analyzed as biomarkers for the detection, monitoring, and follow-up of Fabry disease patients. The sensitivity of the analysis of Ga is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…3 The deacetylated and, therefore, soluble form of Gb3, lyso-Gb3, seems to be a reliable biomarker for both disease progression and therapy efficacy, and can be detected in blood plasma as well as urine. [4][5][6][7][8][9][10] The systemic cellular accumulation of Gb3 leads to progressive renal failure, cardiomyopathy, and recurrent cerebrovascular events, significantly limiting life expectancy in affected patients. 3 The most common cause of death is cardiovascular disease.…”
mentioning
confidence: 99%
“…3 The deacetylated and, therefore, soluble form of Gb3, lyso-Gb3, seems to be a reliable biomarker for both disease progression and therapy efficacy, and can be detected in blood plasma as well as urine. [4][5][6][7][8][9][10] The systemic cellular accumulation of Gb3 leads to progressive renal failure, cardiomyopathy, and recurrent cerebrovascular events, significantly limiting life expectancy in affected patients. 3 The most common cause of death is cardiovascular disease.…”
mentioning
confidence: 99%
“…α-Gal A catalyzes the lysosomal hydrolysis of globotriaosylceramide (Gb-3) to lactosylceramide and digalactosylceramide (Gal-Gal-Cer) to galactosylceramide (Gal-Cer) [57,58]. The deficiency of this enzyme leads to an accumulation of Gb-3, its metabolite, globotriaosylsphingosine (Lyso-Gb-3), and Gal-Gal-Cer in lysosomes (Figure 1) [59]. Detection of Gb-3, Lyso-Gb-3, and Gal-Gal-Cer in urine and plasma are the standard diagnostic methods for FD [58].…”
Section: Fabry Disease Introductionmentioning
confidence: 99%
“…The function of this glycoside hydrolase is to cleave the terminal α-galactosyl moieties from glycoproteins or glycolipids [ 1 ]. The deficiency of the enzyme leads to the accumulation of substrates such as globotriaosylsphingosine (lyso-Gb 3 ), galabiosylceramide (Ga 2 ), and globotriaosylceramide (Gb 3 ) in cells [ 4 ], tissues [ 5 ], and biological fluids [ 6 , 7 , 8 , 9 ]. Different untargeted metabolomic studies performed in our laboratory with urine and plasma specimens from FD patients identified different analogues of lyso-Gb 3 [ 10 , 11 ], as well as analogues/isoforms of Ga 2 [ 12 ] and Gb 3 [ 13 ], as FD biomarkers.…”
Section: Introductionmentioning
confidence: 99%